The service of Bungus Ocean Fishery Port to support tuna industries - Resti Zainal; Nofrizal Nofrizal; Isnaniah Isnaniah (South East Asian Marine Sciences Journal, 2023)
The services of the Bungus Ocean Fishery Port, as the only tuna Fishery port in West Sumatra, support the availability of facilities required by each tuna industry stakeholder. The purpose of this study is to determine the services from the Bungus Ocean Fishery Port that fisheries stakeholders, especially tuna, are currently experiencing: and to determine the level of satisfaction of tuna entrepreneurs with the performance of the Bungus Ocean Fishery Port. The data analysis used is weighting or scoring, and then IPA and CSI analysis is carried out. The results showed that the Bungus Ocean Fishery Port played a good role in providing production activity, infrastructure and public services, and stakeholder’s tuna feel they are quite satisfied with the performance of the Bungus Ocean Fishery Port in supporting the tuna industry and several service attributes of the Bungus Ocean Fisheries port still need to be improved.